Design and Synthesis of Novel PRMT1 Inhibitors and Investigation of Their Effects on the Migration of Cancer Cell - Wang, Caijiao; Dong, Luyao; Zhao, Ziqi; Zhang, Zeqing; Sun, Yutong; Li, Chonglong; Li, Guoqing; You, Xuefu; Yang, Xinyi; Wang, Hao; Hong, Wei (Frontiers in Chemistry, 2022)
Protein arginine methyltransferase 1 (PRMT1) can catalyze the protein arginine methylation by transferring the methyl group from S-adenosyl-L-methionine (SAM) to the guanidyl nitrogen atom of protein arginine, which influences a variety of biological processes including epithelial-mesenchymal transition (EMT) and EMT-mediated mobility of cancer cells. The upregulation of PRMT1 is involved in a diverse range of cancer, such as lung cancer, and there is an urgent need to develop novel and potent PRMT1 inhibitors. In the current manuscript, a series of 2,5-substituted furan derivatives and 2,4-substituted thiazole derivatives were designed and synthesized by targeting at the substrate arginine-binding site on PRMT1, and 10 compounds demonstrated significant inhibitory effects against PRMT1. Among them, the most potent inhibitor, compound 1r (WCJ-394), significantly affected the expression of PRMT1 related proteins in A549 cells and downregulated the expression of mesenchymal markers, by which WCJ-394 inhibited the TGF-β1 induced EMT in A549 cells and prevented the cancer cell migration. The current study demonstrated that WCJ-394 was a potent PRMT1 inhibitor, which could be used as the leading compound for the further drug discovery.